PEMBERDAYAAN MASYARAKAT MELALUI INOVASI TEH DAUN KOPI DI DESA PRINGGAJURANG UTARA, KECAMATAN MONTONG GADING, KABUPATEN LOMBOK TIMUR - Hariadinata, Muhamad; Jurnal Wicara; Marsena, Julia; Hasanah, Uswatun; Aqilah, Syamia; K., Tedy; Ramdani, Egi; Rachim, Nazmi; Salsabila, Andi; Maharani, Shifana; Kusuma, Harry (Jurnal Wicara, 2025)
Pringgajurang Utara Village has abundant coffee plantation potential, but its utilization is not yet optimal because coffee leaves from pruning are only considered waste. In fact, coffee leaves are rich in beneficial compounds such as flavonoids and polyphenols with low caffeine levels. This community service activity aims to empower the villagers through sosialization on processing coffee leaves into economically valuable herbal tea products. The implementation method includes a two-stage socialization, focusing on the coffee plant and the making of tea from coffee leaves. The first socialization focused on coffee cultivation and post-harvest in general, followed by a second socialization on the techniques and stages of coffee leaf tea processing. The processing stages themselves include picking, washing, drying, roasting, crushing, and attractive product packaging. The results of this program showed high enthusiasm from the community. This program succeeded in creating a coffee leaf tea product that can be used as a village's flagship product, thus opening new business opportunities and potentially increasing community income.